Analisa koordinasi simpang bersinyal pada jalan M.H.Thamrin - Prof. H.H.Yamin dan Sutomo – Prof.H.M.Yamin - Prima Pranata Tarigan, Yoel; Mahda Rangkuti, Nuril (Universitas Sulawesi Tenggara, 2025)
How is the performance of Jalan M.H.Thamrin and Jalan Sutomo 2. How is the performance of the two intersections after being coordinated 3. How to compare the performance of the two intersections before and after being coordinated by the research location was carried out on Jalan Prof. H. M. Yamin, the survey will be conducted for 3 days which is divided into 2 working days/weekday and 1 weekend/weekend and data collection will be carried out at the peak time of the vehicle based on the coordination engineering of the two intersections that are simulated obtained a comparison of the performance of the two average intersections in existing conditions (before coordination) and after coordination that has been presented in Table 4.28. The condition of the intersection after coordination is the result of adjusting the Cycel Time Simpang Jalan M.H.Thamrin to Cycel Time Simpang Jalan Sutomo. With the enactment of the intersection coordination engineering that is in this planning can reduce the average saturated degree of average 0.70 to 0.65, reduce the length of the queue which was originally 196.23 meters to 195.07 meters, and can reduce the degree which was originally 32.81 seconds/junior high school with the level of service D to 28.69 seconds/junior high school with the service level D. can be drawn as follows: 1. Cycle Time Existing conditions or before the enactment of the intersection coordination, namely, • M.H.Thamrin Street intersection has a cycle of 82 seconds, •